Skeletal Traction: an Overview of Techniques, Indications, and Considerations - Tri Sastra Pradhini; Dyah Purnaning (Faculty of Medicine, Universitas Mataram, 2024)
Abstract: Traction is a technique aimed at treating bone fractures or dislocations. The application of traction is usually done on the arms, legs, spine, skull, or pelvis, and it is one of the oldest treatment principles in orthopedics. Although it is becoming less commonly used these days, traction still remain as an alternative therapy for patients with fractures. In writing this article, the authors collected several journal articles obtained through searches in the PubMed database and discussed the techniques, indications, drawbacks, advantages, and contraindications of skeletal traction placement, presenting them descriptively. The purpose of writing this article is to provide a general discussion about the indications, techniques, general principles, and considerations to be observed when applying skeletal traction. Through this discussion, it is hoped that it can serve as material for analysis and a source of information regarding skeletal traction.